Development of Oral Cleansing Products Containing Green Tea and Centella asiatica Extracts - Wisuitiprot, Wudtichai; Amornopparattanakul, Nattaporn; Ingkaninan, Kornkanok; Lamlertthon, Supaporn; Waranuch, Neti (Engineering Tribology and Biomedical Materials, 2021)
“Mild” oral care products are needed by some groups of people, such as radiotherapy patients. This study developed oral cleansing products containing green tea (Camelia sinensis (L.) Kuntze) extracts with antibacterial activities and Centella asiatica (L.) Urb. extracts with a wound healing activity. We found that 3.13 mg/ml of green tea extract inhibited both Streptococcus mutans and Candida albicans, which can cause dental caries and oral candidiasis, respectively. Also, a 16 μg/ml C. asiatica extract promoted fibroblast migration in a wound healing study. The products were developed in 2 dosage forms, i.e. a solution and an impregnated gauze, which were isotonic, alcohol and volatile oil free formulations to prevent irritation and burning sensations. The products showed acceptable physical stability after testing under stressed conditions with post-test retention of antimicrobial activity.